A Bacterial Consortium Interacts With Different Varieties of Maize, Promotes the Plant Growth, and Reduces the Application of Chemical Fertilizer Under Field Conditions - Molina-Romero, Dalia; Juárez-Sánchez, Saúl; Venegas, Berenice; Ortíz-González, Cindy S.; Baez, Antonino; Morales-García, Yolanda E.; Muñoz-Rojas, Jesús (Frontiers in Sustainable Food Systems, 2021)
The success of beneficial bacteria in improving the crop growth and yield depends on an adequate plant-bacteria interaction. In this work, the capability of Azospirillium brasilense Sp7, Pseudomonas putida KT2440, Acinetobacter sp. EMM02 and Sphingomonas sp. OF178A to interact with six maize varieties was evaluated by both single-bacterium application and consortium application. The bacterial consortium efficiently colonized the rhizosphere of the autochthonous yellow and H48 hybrid varieties. Bacterial colonization by the consortium was higher than under single-bacterium colonization. The two maize varieties assayed under greenhouse conditions showed increased plant growth compared to the control. The effect of consortium inoculation plus 50% fertilization was compared with the 100% nitrogen fertilization under field conditions using the autochthonous yellow maize. Inoculation with the consortium plus 50% urea produced a similar grain yield compared to 100% urea fertilization. However, a biomass decrease was observed in plants inoculated with the consortium plus 50% urea compared to the other treatments. Furthermore, the safety of these bacteria was evaluated in a rat model after oral administration. Animals did not present any negative effects, after bacterial administration. In conclusion, the bacterial consortium offers a safety alternative that can reduce chemical fertilization by half while producing the same crop yield obtained with 100% fertilization. Decreased chemical fertilization could avoid contamination and reduce the cost in agricultural practices.